Development of Scratch-Based Interactive Media Using the Team Games Tournament Model on the Topic of Algebraic Forms - Purnamasari, Nahlika; Sumartini, Tina Sri; Luritawaty, Irena Puji (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to develop an interactive media based on Scratch that implements the Team Games Tournament (TGT) learning model on the topic of Algebraic Forms. The development process follows the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), which involves five stages: needs analysis, media design, prototype development, implementation, and evaluation. However, due to the researcher's limitations, this study was only conducted up to the Development stage. The developed media was validated by four experts two in the field of mathematics education and two in instructional media engineering. The validation results indicated that the media developed is highly feasible for use in the learning process. Based on expert evaluations, the media is considered effective in enhancing students' understanding of algebraic form concepts and encouraging active interaction and group collaboration through the implementation of the TGT model. Therefore, this Scratch-based interactive media using the TGT model is suitable for supporting mathematics learning on the topic of Algebraic Forms.